Identification and Distribution of Species Culicoides spp. (Diptera: Ceratopogonidae) of Broiler in Banda Aceh - Rusli Rusli; Muhammad Hanafiah (Jurnal Kedokteran Hewan, 2010)
A research has been done to identify the distribution of Culicoides species in Banda Aceh. Culicoides samples were collected by using modified Center for Disease Control (CDC) Miniatur Light Trap. All Culicoides samples has choice a small measured, were identified morfologically. The result showed that the number species Culicoides has caught in Ulee Kareng are: C. huffi, C. arakawae and C. shultzei, whereas in Alue Naga are C. huffi and C. shultzei. The distribution of species Culicoides in Ulee Kareng are: C. huffi has 22, C. arakawae 13 and C. shultzei 11. The average distribution of Culicoides in Alue Naga are C. huffi has 11 and C. shultzei has 4 .